Learning Transformation in the Merdeka Belajar and Kampus Berdampak Era: Synergy of Technology, Pedagogy, and Digital Assessment - Rodika Utama; Dian Artha Kusumaningtyas; Mohamed Yusuf Wako; Asnin Nur Salamah (Universitas Papua, Jurusan Pendidikan Fisika FKIP Unipa, 2026)
The transformation of physics education in the Merdeka Belajar era represents a fundamental paradigm shift in how teachers and students perceive, construct, and apply scientific knowledge. This article presents a theoretical and reflective analysis of the integration of technology, pedagogy, and digital assessment within the context of Indonesian physics education. Using a narrative–reflective approach and a review of recent literature, the study articulates how the Technological Pedagogical and Content Knowledge (TPACK) framework serves as a conceptual foundation for building collaborative, flexible, and scientifically literate learning ecosystems. The findings suggest that the integration of digital tools—such as PhET interactive simulations and Tracker-based video analysis—enhances conceptual understanding, promotes critical thinking, and facilitates continuous formative assessment. Philosophically, Merdeka Belajar embodies not only curricular flexibility but also a humanistic vision of science education that nurtures empathy, social responsibility, and ecological awareness. Therefore, the transformation of physics education is not merely technological modernization but an epistemological reconstruction toward ethical, collaborative, and sustainable learning.